TRANSFORMASI FITRAH DALAM PERSPEKTIF MAQASHID AL-SYARI’AH - Agus Hermanto; Siti Nurjanah; A Kumedi Ja’far (Indonesian Association of Islamic Family Law Lecturers, 2021)
Lesbian, Gay, Bisexual and Transgender (LGBT), often a debate in the midst of globalization, both in the media and in online media, more so in Indonesia with the largest Muslim population in the world, both pro on the grounds of human rights (human rights) or gender. However, this discussion does not recede until here, but rather increasingly sticking out. The study in this study is, what is the view of maqasid al-Shari'ah towards LGBT in Indonesia? The benefit of this research is to know in depth and prove scientifically lgbt actions both normatively and juridically in Indonesia in the perspective of Maqashid al-Shari'ah. This research is a library reseach taken from some opinions of scholars' fiqh both classical and contemporary and the percentage of legislation in Indonesia, more articles that are pro against the LGBT movement. Bahkan MUI telah mengeluarkan Fatwa sejak 2014 Nomor 57 tentang keharaman tindakan LGBT dengan alasan tindakan yang menyalahi firah manusia dan merupakan perbuatan fahisyah. Begitu juga dalam Undang-Undang Nomor 1 tahun 1974 dan Kompilasi Hukum Islam dengan tegas menjelaskan bahwa perkawinan dilakukan oleh seorang laki-laki dan perempuan untuk membina keluarga yang sakinah. Even MUI has issued a Fatwa since 2014 Number 57 on the prohibition of LGBT actions on the grounds of actions that violate human firah and are fahisyah acts. Similarly, in Law No. 1 of 1974 and compilation of Islamic law expressly explains that marriage is performed by a man and a woman to foster a sakinah family.